Neuroleadership in Transforming Educational Leaders - John Albert Dela Rosa (East Asian Journal of Multidisciplinary Research, 2023)
The paper aimed to transform Filipino educational leaders by integrating neuroscience and leadership development. The paper examined and assessed 18 scientific research papers on Neuroleadership techniques and effectiveness, as well as 12 articles on the functions of the brain and its application to educational leadership. From the major results, it appears that social science and neuroscience may be used to comprehend and improve human behavior as an individual and as part of an organization. Neuroleadership also revolutionizes established leadership theories and practices since all of its principles and strategies are scientifically grounded.